The hidden history of international law in the Americas : empire and legal networks - Scarfi, Juan Pablo, 1979- (New York, NY : Oxford University Press, 2017)
This work offers an exploration of the deployment of international law for the legitimization of U.S. ascendancy as an informal empire in Latin America. This text explores the intellectual history of a distinctive idea of American international law in the Americas, focusing principally on the evolution of the American Institute of International Law (AIIL).
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 15, 2017).
Keywords: International law -- America -- History; International law -- United States -- History; Law -- America -- Foreign influences; American Institute of International Law -- History; Law; International law